Caminhos da escrita no Noroeste de Portugal, na Idade Média : alguns aspectos
In the present study, develloped for the International Congress of Paleography, which took place in Vienna, in September 2005, devoted to the study of regional writings, we tried, through the analysis of the rich documentation in the monasteries of Guimarães and S. Simão da Junqueira, to define the dates and constraints of the evolution of cursive and round Visigothic writing, exis- ting in the said monastic institutions, and follow its later transition to Gothic. Unlike the above mentioned documental wealth, the poverty found in the ecclesiastic institutions of the Alto Minho permitted the detection of aspects of cursive and librarian Gothic writing, of cursive humanist of Italian origin, as well as some projections towards and the affirmation of determining aspects of enchained writing.